The trend of analytical approaches in dental research - Kawin Sipiyaruk (2022)
The aims of this article are to examine statistical approaches employed in international dental articles published in 2018 and 2019, as well as to examine relationships among analytical approaches, journal rankings, and types of research. Materials and Methods: International dental journals published in 2018 and 2019 were selected from the four quartiles (Q1-Q4) of journal rankings using a stratified random sampling. All original articles in a randomly sampled issue of each selected journal were reviewed to explore employed statistical approaches and to examine relationships among analytical approaches, journal rankings, and types of research. Results: One hundred and twenty-eight English-written international journals listed according to SCImago Journal Rank were selected, consisting 969 original articles. Significant differences in the use of statistics were found among the four quartiles and between types of research. The articles in Q1 tended to use more advanced analysis but lower descriptive analytics than other quartiles. The narrative approach was highly used in laboratory-based articles (18.66%), whereas clinical research was likely to use more descriptive (92.32%) and advanced analyses (26.30%). The data also found no remarkable differences in the patterns of the three most common statistical use among the four quartiles. Conclusion: This research revealed statistical use in international dental journals, which will enable educators to consider statistical content to be included in dental curricula, either for undergraduate or for postgraduate programs.